2019
DOI: 10.14338/ijpt-18-00046.1
|View full text |Cite
|
Sign up to set email alerts
|

Large Malignant Fibrous Histiocytoma Treated with Hypofractionated Proton Beam Therapy and Local Hyperthermia

Abstract: Purpose: Malignant fibrous histiocytoma (MFH) is one of the most common soft tissue sarcomas. The standard treatment is adequate surgical resection; in addition, radiation therapy plays a major role in perioperative treatment in most cases. Herein, we report the case of a patient with a large MFH who was successfully treated with combined proton beam therapy (PBT) and local hyperthermia (LH). Case Presentation: A 60-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The SEER database contains data from more than 20 regions and covers 28% of the US population. 6 It collects sociodemographic, clinicopathological, treatment, follow-up, and other information on cancer patients. 30 This can provide high-quality, multicenter, large-sample data for the study of rare cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SEER database contains data from more than 20 regions and covers 28% of the US population. 6 It collects sociodemographic, clinicopathological, treatment, follow-up, and other information on cancer patients. 30 This can provide high-quality, multicenter, large-sample data for the study of rare cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Undifferentiated pleomorphic sarcoma occurs most frequently in the soft tissues of extremities (50% in lower limbs, 20% in upper limbs), and occasionally in bone and viscera. [5][6][7][8] It peaks around the age of 60 years and is more common in males. 6 As one of the most common subtypes, it accounts for about 5-10% of the adult soft-tissue sarcoma (STS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number single case studies of hypofractionated PBT have been reported since 2017 [58][59][60]. Seidensaal et al published a study protocol to compare the outcomes of hypofractionated PBT vs carbon ion therapy for neoadjuvant irradiation of retroperitoneal soft tissue sarcoma [61].…”
Section: Miscellaneousmentioning
confidence: 99%
“…Although particle therapy has significant advantages over conventional RT for treating cancer by reducing the radiation damage to surrounding normal tissues, the radiation dose deposited by the particle beam in normal tissues which locates in the path before the tumor is unavoidable, which may cause normal tissue damage [ 10 ]. Many strategies have been suggested to balance treatment outcome of conventional RT with side effects, such as increasing radiation resistance in healthy tissues by using a very high-dose-rate (>40 Gy/s) RT (known as FLASH RT) [ 11 , 12 ], reversing tumor tissue radiation resistance using synergistic therapeutics [ 13 , 14 , 15 , 16 ], increasing radiation sensitization, and limiting radiation dose deposition in the tumor using nanosensitizing agents [ 17 , 18 , 19 ]. Of these, metal-based nanomaterials or “nano-radioenhancers” (NREs) have attracted significant attention in radiation oncology because of their strong photoelectric absorption coefficients for high atomic number (Z) metallic elements [ 20 ].…”
Section: Introductionmentioning
confidence: 99%